2020
DOI: 10.1007/s12288-020-01282-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hematological Indices as a Screening Tool of Beta Thalassemia Trait in Eastern Uttar Pradesh: An Institutional Study

Abstract: A large majority of microcytic hypochromic anemia have defects in cellular hemoglobin synthesis due to either iron deficiency or thalassemia trait; both differing in management and prognosis. HPLC and serum iron profile as confirmatory tests are unavailable at health care centers. Blanket therapy of iron supplements is therefore given in all such cases which may cause iron overload in thalassemia cases. Easy to use and cost effective screening methods are desirable. The present study was undertaken to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Previous studies reported different sensitivities and specificities for the formulas we evaluated in this study which can be attributed to the differences in the distribution of hemoglobin b-subunit mutations, since each population has its specific distribution which is more likely may affect RBC indices and so the performance of these mathematical formulas [36] [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported different sensitivities and specificities for the formulas we evaluated in this study which can be attributed to the differences in the distribution of hemoglobin b-subunit mutations, since each population has its specific distribution which is more likely may affect RBC indices and so the performance of these mathematical formulas [36] [37] .…”
Section: Discussionmentioning
confidence: 99%
“…The beta-thalassemia trait in Wickramaratne KAC et al was diagnosed mainly based on the HPLC screening with HbA2 levels between 3.5% and 7.5% were considered as beta-thalassemia trait and non-beta-thalassemia trait with HbA2 levels less than 3.5%. A cross-sectional study conducted by Bhargava et al showed the occurrence of beta-thalassemia trait cases was 6.7% as depicted in Table 7 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent form of the disease is the BTT. There is a significant disparity in the prevalence of BTT throughout India's various regions: 6.5% in the state of Punjab, 8.4% in the state of Tamil Nadu, 4.3% in southern India, and 3.5% in the state of Bengal [9]. In different Indian states, the prevalence of the BTT ranged from 1.48% to 3.64%, totaling 2.78% [10].…”
Section: Discussionmentioning
confidence: 99%